Examining the Mediating Role of Employee Well-Being in the Relationship Between Job Satisfaction and Performance - Gülsen Topaktaş; Yasin Aras; Oğuz Işık (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study aimed to investigate the relationship between job satisfaction and job performance among healthcare workers, with employee well-being serving as a mediating variable.Materials and Methods: A quantitative data collection approach was adopted using a questionnaire consisting of four sections. The sample of the study consisted of 203 healthcare workers employed in a public health institution operating in Ankara.Results: The analysis revealed a significant positive relationship between job satisfaction and individual job performance, as well as between job satisfaction and employee well-being among healthcare workers. Furthermore, employee well-being was found to have a significant mediating role in the relationship between job satisfaction and job performance.Conclusion: Higher levels of job satisfaction among healthcare workers were associated with increased employee well-being, which, in turn, was associated with enhanced job performance. These findings highlight the important role of employee well-being as a mechanism linking job satisfaction and performance outcomes. Accordingly, healthcare organizations should place greater emphasis on promoting employee well-being as a strategic priority. Managers and policymakers are encouraged to implement targeted initiatives to support employee well-being, thereby fostering a more satisfied, engaged, and productive healthcare workforce.